Preparation method of copper-doped binary manganese-based layered oxide positive electrode material, positive electrode material and application

Through the copper-doped binary manganese-based layered oxide positive electrode material, the average valence state and layer spacing of Mn are adjusted, and the Jahn-Teller effect is suppressed, which solves the problem of insufficient performance of manganese-based layered oxide in potassium ion batteries, achieving high specific capacity and excellent electrochemical performance.

CN119660810AActive Publication Date: 2025-03-21ZHONGYU PEGASUS NEW MATERIALS TECH INNOVATION CENT (ZHENGZHOU) CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411876124.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-21
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The poor circulation performance, poor rate performance and low actual capacity of manganese-based layered oxides in potassium ion batteries limit their commercial applications.

Method used

A P3 phase was synthesized through copper doping, with a high Mn4+/Mn3+ ratio, adjusting the average valence state of Mn, suppressing the Jahn-Teller effect, and widening the layer spacing through Cu2+ to accelerate the diffusion of K+.

Benefits of technology

It achieves high specific capacity, stable structure and excellent electrochemical performance, and improves the cycle stability and rate performance of potassium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119660810A_ABST
    Figure CN119660810A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a copper-doped binary manganese-based layered oxide positive electrode material, the positive electrode material and application. A copper salt is used as a dopant, a copper element is doped into a manganese-based oxide by adopting a sol-gel method to obtain a precursor solution, and then the precursor solution is subjected to high-temperature heat treatment to obtain the positive electrode material of the copper-doped binary manganese-based layered oxide. The preparation method comprises the following steps: (1) adding various sylvite, manganese salt, copper salt, a binder and acid into deionized water, and stirring until the materials are completely dissolved to obtain a precursor; and (2) drying the solution obtained in the step (1). And (3) grinding the fluffy solid dried in the step (2) into fine particles. And (4) carrying out high-temperature calcination on fine particles obtained by grinding in the step (3) to obtain copper-doped binary manganese-based layered oxide positive electrode material powder. The method has the characteristics of simple process, low cost and large-scale production, and the positive electrode material as the positive electrode of the potassium ion battery has high specific capacity, good cycling stability and excellent rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemistry, and in particular relates to a preparation method of a copper-doped binary manganese-based layered oxide positive electrode material, a positive electrode material and an application thereof. Technical Background

[0002] Lithium-ion batteries (LIBs) are widely used in mobile electronic devices, electric vehicles, and energy storage due to their high energy density and excellent performance. However, lithium-ion batteries have some limitations, such as limited resources and high costs. Therefore, researchers have begun to explore other alkali metal ion batteries as alternatives, among which potassium ion batteries have attracted much attention due to their abundant resources, high energy density, and easy commercialization. However, due to the fact that K + Ions have a large ionic radius, and their embedding / de-embedding process will cause serious damage to the material skeleton structure, seriously affecting the actual rate performance and cycle life of PIBs. Therefore, it is necessary to study a method for + Potassium ion positive electrode material with a stable framework structure after deintercalation.

[0003] In recent years, the research on PIBs cathode materials has made significant progress, and the number of literature reports has gradually increased. The reported PIBs cathode materials are divided into four categories: layered transition metal oxides, metal hexacyanometallates, organic compounds and polyanion compounds. Metal hexacyanometallate compounds, such as Prussian blue (white), have a very high specific capacity, but the electronic conductivity of the material is poor, and the rate performance is difficult to improve. Organic electrode materials have the advantages of being renewable, green, and having a high capacity, but they have high solubility in the electrolyte and poor conductivity, which greatly limits the application of organic cathode materials in PIBs. Polyanion compounds generally have high electrochemical reaction stability and operating voltage, but the disadvantage is that the ionic and electronic conductivity of such materials is low, and the larger molecular weight will also reduce the specific capacity. Among these candidate materials, layered transition metal oxides (A x MO 2 , A=K, Na and their combinations; M=V, Mn, Fe, Ni, Cr, Co and their combinations) are particularly promising because of their unique layered structure, which can accommodate larger potassium ion insertion and extraction, and their simple synthesis method and high output voltage make them good cathode materials for potassium ion batteries.

[0004] Among layered transition metal oxides, manganese-based layered oxides have the advantages of low cost and environmental friendliness, as well as a stable crystal structure. When the layered oxide contains a relatively large amount of manganese, the structure of the material is relatively stable, the synthesis is relatively easy, and phase separation is not easy to occur. Therefore, manganese-based layered oxides have been widely studied in potassium ion battery positive electrode materials. Despite this, manganese-based layered oxides still face problems such as poor cycle performance, poor rate performance, and low actual capacity, which limits their future commercial application.

[0005] The main reason for the poor cycle performance is essentially the Jahn-Teller effect in manganese-based layered oxides. Generally, manganese in the material exists in a mixed valence state of +3 and +4. 4+ ) will not produce the Jahn-Teller effect, forming a distortion-free [MnO 6 ] octahedron, thus obtaining a stable crystal structure. However, in the 3d electron orbital there is (t2g) 3 (eg) 1 The electronic configuration of high-spin trivalent manganese (Mn 3+ ) will produce the Jahn-Teller effect. This Jahn-Teller effect will cause [MnO 6 ] The octahedron is distorted, reducing the symmetry and energy of the nonlinear molecular system, leading to structural disorder and strong internal stress, and ultimately causing instability in the crystal structure. In addition, during the charge and discharge process, the valence state of manganese will change between +3 and +4, causing the Jahn-Teller effect in the material to be repeatedly eliminated and generated, ultimately leading to an irreversible multiphase transition process, further affecting the structural stability of the material.

[0006] In order to solve these problems, researchers have tried a variety of strategies, such as element doping, surface coating, core-shell structure, etc. Among them, element doping is an effective strategy to solve the above problems. Commonly used doping elements include Mg, Ni, Ti, etc. The doping of these elements has a significant effect on the overall structure and performance of the material. The use of copper, which has a wide range of sources, can improve the structural stability of the material itself, improve its rate performance, and effectively save costs, which can be better commercialized.

[0007] Therefore, the synthesis of copper-doped binary manganese-based layered oxide positive electrode materials is of great significance to promote the development of high specific energy and high stability potassium ion batteries. Summary of the invention

[0008] The purpose of the present invention is to adjust the average valence state of Mn to suppress the Jahn-Teller effect of the manganese-based layered oxide positive electrode, synthesize a P3 phase with high Mn by copper doping 4+ / Mn3+ The invention discloses a cathode material for potassium ion batteries with high specific capacity and high stability, which has simple process, low cost and can be mass-produced. The Jahn-Teller effect of manganese-based layered oxide cathode is suppressed by adjusting the average valence state of Mn, thereby improving its cycle stability. The preparation method of the cathode material for potassium ion batteries (PIBs) with high specific capacity and high stability is obtained, and the material can be used as the cathode material for potassium ion batteries with high specific energy and long life.

[0009] The technical solution of the present invention to solve the above problems is: a P3 phase layered structure with high specific capacity is synthesized by appropriate material ratio, and a high Mn 4+ / Mn 3+ ratio, which increases the average valence state of Mn and suppresses the Jahn-Teller effect. 2+ The interlayer spacing is widened in the layered structure, accelerating K + diffusion, promoting the kinetics of ion diffusion.

[0010] The method for preparing the material comprises the following steps:

[0011] (1) adding various potassium salts, manganese salts, copper salts, and a binder to deionized water, and stirring with acid until completely dissolved to obtain a precursor;

[0012] (2) drying the solution obtained in step (1);

[0013] (3) grinding the fluffy solid dried in step (2) into fine particles;

[0014] (4) calcining the fine particles obtained by grinding in step (3) at high temperature to finally obtain a copper-doped binary manganese-based layered oxide positive electrode material;

[0015] According to the above scheme, in step (1), the potassium salt is potassium nitrate, the manganese salt is manganese acetate tetrahydrate, the copper salt is copper acetate monohydrate, the binder is polyvinyl pyrrolidone (PVP K90, Mw=1 300 000), and the acid is oxalic acid.

[0016] According to the above scheme, the amount of potassium salt in step (1) should be 5% in excess, and PVP should be added in batches between the additions of various materials.

[0017] According to the above scheme, the synthesis process in step (1) is heated and stirred in a water bath, the stirring speed is 400-600 r / min, the heating temperature is 60-80° C., and the duration is 5-6 h.

[0018] According to the above scheme, the drying temperature in step (3) is 110-140° C. and the drying time is 10-13 h.

[0019] According to the above scheme, the calcination atmosphere in step (4) is air, the pre-calcination temperature is 490-500°C, the heating rate is 5-6°C / min, the calcination time is 2-3h, and then the final calcination temperature is 900-920°C, the heating rate is 5-6°C / min, and the calcination time is 12-14h.

[0020] The present invention has the following benefits:

[0021] (1) Stable P3 phase layered structure materials were synthesized.

[0022] (2) The average valence state of Mn was increased, the Jahn-Teller effect was inhibited, and the diffusion rate of potassium ions was increased.

[0023] (3) Taking into account high capacity, high rate and high stability, the assembled half-cell exhibits excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is the XRD diagram of the product of Example 2 and the product of Example 1 of the present invention.

[0025] Figure 2 This is the XPS chart of Mn2p of the product of Example 2 of the present invention.

[0026] Figure 3 This is the XPS graph of Cu2p of the product of Example 2 of the present invention.

[0027] Figure 4 It is the charge and discharge curve of the half-cell assembled with the positive electrode material obtained in Example 2 of the present invention at different numbers of cycles at a current density of 200 mA / g.

[0028] Figure 5 It is a comparison chart of the rate performance of half-cells assembled with the positive electrode materials obtained in Example 2 and Example 1 of the present invention at different current densities.

[0029] Figure 6 It is a comparison chart of the cycle performance of half-cells assembled with the positive electrode materials obtained in Example 2 and Example 1 of the present invention after 100 cycles at a current density of 100 mA / g.

[0030] Figure 7 This is a cycle performance diagram of the half-cell of Example 2 of the present invention after 700 cycles at a high current density of 1 A / g.

[0031] Figure 8 It is a comparison diagram of the electrochemical impedance of half-cells assembled with the positive electrode materials obtained in Example 2 and Example 1 of the present invention. DETAILED DESCRIPTION

[0032] In order to better understand the present invention, the content of the present invention is further explained in conjunction with the following embodiments, but the content of the present invention is not limited to the following embodiments. The technical solution of the present invention is explained in conjunction with the accompanying drawings and embodiments.

[0033] A method for preparing a copper-doped binary manganese-based layered oxide positive electrode material comprises the following steps:

[0034] (1) Add various potassium salts, manganese salts, copper salts, binders, and acids into deionized water and stir until they are completely dissolved to obtain a precursor.

[0035] (2) drying the solution obtained in step (1).

[0036] (3) Grinding the fluffy solid dried in step (2) into fine particles.

[0037] (4) The fine particles obtained by grinding in step (3) are calcined at high temperature to finally obtain a copper-doped binary manganese-based layered oxide positive electrode material.

[0038] In step (1), the potassium salt is potassium nitrate, the manganese salt is manganese acetate tetrahydrate, the copper salt is copper acetate monohydrate, the binder is polyvinyl pyrrolidone, and the acid is oxalic acid.

[0039] The binder used is polyvinyl pyrrolidone K90 (PVP K90), which has a molecular weight of 1,300,000 (Mw = 1,300,000); in step (1), the amount of potassium salt used should exceed the calculated amount by 5%, and polyvinyl pyrrolidone (PVP) should be added in batches between the addition of various materials. Oxalic acid is used to neutralize excess by-products, and potassium nitrate (KNO 3 ), tetrahydrate and manganese acetate (C 4 H 14 MnO 8 ), monohydrate and copper acetate (Cu(CO 2 CH 3 ) 2 ·H 2 The dosage of O) is calculated as follows:

[0040] In the chemical formula K of Example 1 discussed below 0.5 Mn 0.9 Cu 0.1 O 2The required element K:Mn:Cu ratio is 0.5:0.9:0.1mmol. For the convenience of weighing, it is converted to 1:1.8:0.2mmol. The mass ratio is 1.01103g:4.65671g:0.19965g. Furthermore, the amount of potassium nitrate used must exceed the calculated amount (1.01103g) by 5%, so the actual amount of potassium nitrate used is 1.06155g (heating and stirring in a water bath will cause the potassium salt to volatilize).

[0041] The chemical formula of Example 2 discussed below is K 0.5 Mn 0.95 Cu 0.05 0 2 , similar to the above description, first of all, the element ratio K: Mn: Cu is 0.5: 0.95: 0.05, for the convenience of weighing is 1: 1.9: 0.1, so the three materials potassium nitrate KNO 3 , tetrahydrate and manganese acetate C 4 H 14 MnO 8 , monohydrate and copper acetate Cu(CO 2 CH 3 ) 2 ·H 2 The molar ratio of O is also 1:1.9:0.1mmol, which is converted into a mass ratio of 1.01103g:4.41162g:0.3993g. Furthermore, the amount of potassium nitrate used must exceed the calculated amount (1.01103g) by 5%, so the actual amount of potassium nitrate used is 1.06155g.

[0042] In Example 3 discussed below, the chemical formula K 0.5 Mn 0.85 Cu 0.15 O 2 , K:Mn:Cu=0.5:0.85:0.15, for the convenience of weighing, it is converted to 1:1.7:0.3, and the mass ratio is 1.01103g:4.16653g:0.59895g. Moreover, the amount of potassium nitrate used must exceed the calculated amount (1.01103g) by 5%, so the actual amount of potassium nitrate used is 1.06155g. Furthermore, in the specific order of addition, PVP is a binder. Adding it all at once will cause it to clump itself, and its adhesion to other substances is not so good. Adding it in batches can be stirred and bonded at the same time. Oxalic acid and potassium nitrate are added first and last, and the order of the two substances in the middle, manganese acetate tetrahydrate, monohydrate and copper acetate, can be swapped.

[0043] In step (1), the synthesis process is heated and stirred in a water bath, the stirring speed is 400-600 r / min, the heating temperature is 60-80° C., and the duration is 5-6 hours.

[0044] In step (3), the drying temperature is 110-140° C. and the drying time is 10-13 hours.

[0045] In step (4), the calcination atmosphere is air, the pre-calcination temperature is 490-500°C, the heating rate is 5-6°C / min, the calcination time is 2-3h, and then the final calcination temperature is 900-920°C, the heating rate is 5-6°C / min, and the calcination time is 12-14h. After the pre-calcination in step (4), grinding is performed once, and the final calcination is cooled to 150-200°C and quickly transferred to a glove box for storage.

[0046] The present solution relates to a copper-doped binary manganese-based laminated positive electrode material, and the copper-doped binary manganese-based laminated positive electrode material is prepared by the above-mentioned preparation method.

[0047] The present invention relates to a copper-doped binary manganese-based layered positive electrode material, in which the molar ratio of the doped metal element copper to the matrix manganese element is 1:9.

[0048] The present solution relates to the use of a copper-doped binary manganese-based layered positive electrode material as claimed in the claim as a positive electrode material for a potassium ion battery.

[0049] Example 1

[0050] The method for preparing a copper-doped binary manganese-based layered oxide positive electrode material comprises the following steps:

[0051] (1) Add 4g oxalic acid, 1g PVP, 4.65671g manganese acetate tetrahydrate, 1g PVP, 0.19965g copper acetate monohydrate, 1g PVP, 1.06155g potassium nitrate, and 1g PVP to 40ml deionized water under continuous stirring, and heat in a water bath. The heating temperature is 70°C, the speed is 500r / min, and the stirring is continued for 5h.

[0052] (2) The solution obtained in (1) was transferred into a 100 ml corundum crucible, sealed with aluminum foil and small holes were poked on the crucible for ventilation, and then placed in an oven at 120°C for drying for 12 h.

[0053] (3) The fluffy sponge-like solid obtained in (2) is scraped off the crucible, transferred to a mortar and ground thoroughly to obtain fine particles.

[0054] (4) The mixed particles in (3) are placed in a porcelain boat, and the porcelain boat is placed in a muffle furnace. The temperature is increased to 500°C at a heating rate of 5°C / min in an air atmosphere and kept at this temperature for 2 hours. The mixture is taken out for secondary grinding, and then the temperature is increased to a final temperature of 900°C at a heating rate of 5°C / min and kept at this temperature for 12 hours. After annealing, a copper-doped binary manganese-based hierarchical oxide positive electrode material is obtained (in this process, the sample needs to be promptly transferred to an argon glove box for storage when the temperature in the muffle furnace drops to 100-150°C).

[0055] Example 2

[0056] The method for preparing a copper-doped binary manganese-based layered oxide positive electrode material comprises the following steps:

[0057] (1) Add 4g oxalic acid, 1g PVP, 4.41162g manganese acetate tetrahydrate, 1g PVP, 0.3993g copper acetate monohydrate, 1g PVP, 1.06155g potassium nitrate, and 1g PVP to 40ml deionized water under continuous stirring, and heat in a water bath. The heating temperature is 70°C, and the speed is 500r / min and stirred for 5h.

[0058] (2) The solution obtained in (1) was transferred into a 100 ml corundum crucible, sealed with aluminum foil and small holes were poked on the crucible for ventilation, and then placed in an oven at 120°C for drying for 12 h.

[0059] (3) The fluffy sponge-like solid obtained in (2) is scraped off the crucible, transferred to a mortar and ground thoroughly to obtain fine particles.

[0060] (4) The mixed particles in (3) are placed in a porcelain boat, and the porcelain boat is placed in a muffle furnace. The temperature is increased to 500°C at a heating rate of 5°C / min in an air atmosphere and kept at this temperature for 2 hours. The mixture is taken out for secondary grinding, and then the temperature is increased to a final temperature of 900°C at a heating rate of 5°C / min and kept at this temperature for 12 hours. After annealing, a copper-doped binary manganese-based hierarchical oxide positive electrode material is obtained (in this process, the sample needs to be promptly transferred to an argon glove box for storage when the temperature in the muffle furnace drops to 100-150°C).

[0061] Example 3

[0062] The method for preparing a copper-doped binary manganese-based layered oxide positive electrode material comprises the following steps:

[0063] (1) Add 4g oxalic acid, 1g PVP, 4.16653g manganese acetate tetrahydrate, 1g PVP, 0.59895g copper acetate monohydrate, 1g PVP, 1.06155g potassium nitrate, and 1g PVP to 40ml deionized water under continuous stirring, and heat in a water bath. The heating temperature is 70°C, and the speed is 500r / min and stirred for 5h.

[0064] (2) The solution obtained in (1) was transferred into a 100 ml corundum crucible, sealed with aluminum foil and small holes were poked on the crucible for ventilation, and then placed in an oven at 120°C for drying for 12 h.

[0065] (3) The fluffy sponge-like solid obtained in (2) is scraped off the crucible, transferred to a mortar and ground thoroughly to obtain fine particles.

[0066] (4) The mixed particles in (3) are placed in a porcelain boat, and the porcelain boat is placed in a muffle furnace. The temperature is increased to 500°C at a heating rate of 5°C / min in an air atmosphere and kept at this temperature for 2 hours. The mixture is taken out for secondary grinding, and then the temperature is increased to a final temperature of 900°C at a heating rate of 5°C / min and kept at this temperature for 12 hours. After annealing, a copper-doped binary manganese-based hierarchical oxide positive electrode material is obtained (in this process, the sample needs to be promptly transferred to an argon glove box for storage when the temperature in the muffle furnace drops to 100-150°C). Electrode material preparation and assembly process: 70 mg of the prepared copper-doped binary manganese-based layered oxide positive electrode material, 20 mg of Super P, and 10 mg of PVDF5130 were mixed and dispersed in 900 μl of N-methylpyrrolidone, and the above materials were transferred to a ball mill containing 5 large (d = 3 mm) and 5 small (d = 2 mm) zirconium oxide ball milling beads. A high-speed vibration ball mill was used with a vibration frequency of 4000 r / min. After ball milling for 2 minutes, it was cooled for 1 minute and ball milled for 2 minutes to form a uniform slurry. Then, a 6.5×6.5 cm square was drawn on aluminum foil, and the slurry was evenly coated in the square. Then, it was dried on a heating table at 70-80°C for 10-12 hours to obtain the positive electrode material. The electrode sheet was made by cutting the aluminum foil into electrode discs with a diameter of 8 mm. The mass loading of the active material of the cut electrode sheet was 1.5-2.5 mg / cm 2 The negative electrode is made of potassium metal, with a diameter of 12 mm, and the glass fiber separator is Whatman GF / D, with a KPF of 0.8 mol / L. 6 Ethylene carbonate (EC) and diethyl carbonate (DEC) dissolved in a volume ratio of 1:1 were used as an electrolyte and assembled into a CR2016 button cell in an argon atmosphere glove box, and the electrochemical performance of the cell was tested (1.5-3.9V).

[0067] The K prepared in Example 2 0.5 Mn 0.9 Cu 0.1 O 2 The XRD pattern of the product is as follows Figure 1 As shown, the XRD pattern shows that K 0.5 Mn 0.9 Cu 0.1 O 2It is a P3 phase layered material, does not contain any impurities, and belongs to the R-3m space group (PDF#30-0950). The (101) characteristic peak of the product of Example 2 and the product of Example 1 shifts to a small angle, proving that the interlayer spacing of the material prepared in Example 2 is greater than that of the product of Example 1, which is more conducive to the deintercalation of potassium ions. 0.5 Mn 0.9 Cu 0.1 O 2 The XPS picture of the product is as follows Figure 2 and Figure 3 As shown, Mn in Example 2 4+ / Mn 3+ The ratio is greater than that of Example 1, indicating that the average valence of Mn has been adjusted, and the adjustment degree of Example 2 is better than that of Example 1, and Cu is successfully doped and the valence state does not change. 0.5 Mn 0.9 Cu 0.1 O 2 The charge and discharge curves of the button cell assembled with the electrode material and potassium metal at different cycles at 200mA / g are as follows Figure 4 As shown in the figure, the discharge specific capacity is as high as 85.5 mAh / g, and the charge and discharge curves are basically the same, proving that it has excellent cycle charge and discharge capabilities. 0.5 Mn 0.9 Cu 0.1 O 2 The rate performance of button cells assembled with electrode materials and potassium metal at different current densities is shown in Figure 2. Figure 5 As shown in the figure, when the current density gradually increases from 50 mA / g to 100, 200, 500, 1000 and then back to 100 mA / g, its specific capacity is 106.8, 91.1, 85.3, 68.2, 60.8, 91.4 mAh / g, respectively, showing that it has excellent rate performance. 0.5 Mn 0.9 Cu 0.1 O 2 The cycling performance of the button cell assembled with the electrode material and potassium metal at a current density of 100 mA / g is shown in Figure 6 As shown in the figure, after 100 cycles, it still has a specific capacity of 74.2 mAh / g, and the capacity retention rate is 82.3%, which proves that it has excellent cycle stability. 0.5 Mn 0.9 Cu 0.1 O 2 The cycling performance of the button cell assembled with the electrode material and potassium metal at a high current density (1000 mA / g) is as follows Figure 7As shown in the figure, after 700 cycles, it still has a specific capacity of 42 mAh / g, and the capacity retention rate is 66%, proving its excellent high current cycling performance. 0.5 Mn 0.9 Cu 0.1 O 2 The electrochemical impedance spectroscopy of the button cell assembled with the electrode material and potassium metal is shown in Figure 8 As shown, it indicates that its charge transfer impedance is low and the degree of polarization is small, which is beneficial to improving the charging and discharging capacity.

[0068] The K prepared in this Example 1 0.5 Mn 0.95 Cu 0.05 O 2 The XRD pattern of the product is as follows Figure 1 As shown, the XRD pattern shows that K 0.5 Mn 0.95 Cu 0.05 O 2 It is also a P3 phase layered material, does not contain any impurities, and belongs to the R-3m space group (PDF#30-0950).

[0069] The K prepared in Example 1 0.5 Mn 0.95 Cu 0.05 O 2 The rate performance of button cells assembled with electrode materials and potassium metal at different current densities is as follows Figure 6 As shown in the figure, when the current density gradually increases from 50 mA / g to 100, 200, 500, 1000 and then back to 100 mA / g, the specific capacities are 95.7, 84.6, 73.5, 60.3, 45.6 and 82.7 mAh / g, respectively, showing poor rate performance. 0.5 Mn 0.95 Cu 0.05 O 2 The cycling performance of the button cell assembled with the electrode material and potassium metal at a current density of 100 mA / g is shown in Figure 7 As shown in the figure, after 100 cycles, the capacity retention rate rapidly decayed to 68.2%, proving that its cycle performance is poor. 0.5 Mn 0.95 Cu 0.05 O 2 The electrochemical impedance diagram of the button cell assembled with the electrode material and potassium metal shows a large charge transfer impedance and severe polarization phenomenon.

[0070] In summary, the preparation of copper-doped binary manganese-based hierarchical oxide positive electrode materials is simple and cost-effective for large-scale production. The prepared copper-doped binary manganese-based hierarchical oxide positive electrode material has a highly ordered layered structure, an increased average valence state of Mn and a large interlayer spacing, which inhibits the Jahn-Teller effect, promotes the diffusion capacity of potassium ions, and enhances structural stability. It is one of the candidates for the next generation of high specific energy, fast charging, and long-life potassium ion battery positive electrode materials. In general, the present invention provides a preparation method and application of copper-doped binary manganese-based hierarchical oxide positive electrode materials. Using copper salt as a dopant, copper element is doped into manganese-based oxide by a sol-gel method to obtain a precursor solution, and then a copper-doped binary manganese-based hierarchical oxide positive electrode material is obtained by high-temperature heat treatment. The preparation process is as follows: (1) Various potassium salts, manganese salts, copper salts, and binders are added to deionized water, and acid is stirred until completely dissolved to obtain a precursor. (2) The solution obtained in (1) is dried. (3) The fluffy solid obtained after drying in (2) is ground into fine particles. (4) The fine particles obtained by grinding in (3) are calcined at high temperature to finally obtain copper-doped binary manganese-based layered oxide positive electrode material powder. The present invention has the characteristics of simple process, low cost and large-scale production. The copper-doped binary manganese-based positive electrode material has high specific capacity, good cycle stability and excellent rate performance as a positive electrode of a potassium ion battery.

Claims

1. A method for preparing a copper-doped binary manganese-based layered oxide positive electrode material, characterized in that: The following steps are included: (1) adding various potassium salts, manganese salts, copper salts, binders, and acids to deionized water and stirring until completely dissolved to obtain a precursor; (2) drying the solution obtained in step (1); (3) grinding the fluffy solid dried in step (2) into fine particles; (4) calcining the fine particles obtained by grinding in step (3) at high temperature to finally obtain a copper-doped binary manganese-based layered oxide positive electrode material; In step (1), the potassium salt is potassium nitrate, the manganese salt is manganese acetate tetrahydrate, the copper salt is copper acetate monohydrate, the binder is polyvinyl pyrrolidone, and the acid is oxalic acid.

2. The method for preparing the copper-doped binary manganese-based layered positive electrode material according to claim 1, characterized in that In step (1), the amount of potassium salt used should exceed the calculated amount by 5%, and polyvinyl pyrrolidone should be added in batches between the additions of various materials.

3. The method for preparing the copper-doped binary manganese-based layered positive electrode material according to claim 1, characterized in that The synthesis process in step (1) is heated and stirred in a water bath, the stirring speed is 400-600 r / ·in, the heating temperature is 60-80° C., and the duration is 5-6 hours.

4. The method for preparing the copper-doped binary manganese-based layered positive electrode material according to claim 1, characterized in that In step (3), the drying temperature is 110-140° C. and the drying time is 10-13 hours.

5. The method for preparing the copper-doped binary manganese-based layered positive electrode material according to claim 1, characterized in that In step (4), the calcination atmosphere is air, the pre-calcination temperature is 490-500°C, the heating rate is 5-6°C / min, the calcination time is 2-3h, and then the final calcination temperature is 900-920°C, the heating rate is 5-6°C / min, and the calcination time is 12-14h.

6. The method for preparing the copper-doped binary manganese-based layered positive electrode material according to claim 1, characterized in that After the pre-calcination in step (4) is completed, grinding is performed once, and after the final calcination is cooled to 150-200°C, it is quickly transferred to a glove box for storage.

7. A copper-doped binary manganese-based layered positive electrode material, characterized in that: A copper-doped binary manganese-based layered positive electrode material is prepared by the preparation method described in any one of claims 1 to 7.

8. The copper-doped binary manganese-based positive electrode material according to claim 7, characterized in that The molar ratio of the doped metal element copper to the matrix manganese element is 1:

9.

9. Use of the copper-doped binary manganese-based layered positive electrode material as claimed in claims 7-8 as a positive electrode material for a potassium ion battery.

Citation Information

Patent Citations

  • High-specific-surface-area Fischer-Tropsch synthesis catalyst and preparation method and application of high-specific-surface-area Fischer-Tropsch synthesis catalyst

    CN104624196A

  • Copper-doped potassium manganate electrode material, preparation method thereof and application of material in potassium ion battery

    CN112531169A

  • Copper-doped potassium manganate electrode material, preparation method thereof and application of copper-doped potassium manganate electrode material in potassium ion battery

    CN114628677A

  • Copper-doped modified P3-phase potassium ion battery manganese-based layered positive electrode material and preparation method thereof

    CN115602840A

  • Preparation method of high-entropy manganese-based potassium ion battery positive electrode material

    CN117819611A